Analisis Prestasi Belajar Matematika Peserta Didik Kelas XI SMKN 5 Mataram Ditinjau Dari Kepribadian Ekstrovert Dan Introvert Tahun Pelajaran 2019/2020 - Millita Ummul Fathonah; Arjudin Arjudin; Nani Kurniati (Indonesian Publication Center, 2021)
Learning is a change of behaviour which is relatively stay in an individual as an impact from their experience. The result of a learning process show the student achievement for the effort they have done and will be given by the teacher in number or alphabet form. One of the things that affects the student learning achievement is non-intellectual factor that is personality factor. SMKN 5 Mataram is one of school that has student with varying personalities and achievements. Because of this, analysis of student’s mathematics achievement based on personalities has to be done. The research type used was causal-comparative research (ex post facto) with purposive sampling technique. This research used quantitative data analysis (descriptive and inferential analysis) and qualitative data analysis. As for the hypothesis test which used one way anova test with the help of SPSS21, obtained that the value of Fcount= 2.361 < Ftabel = 3.92 so that H0 was accepted. Consequently, it can be concluded that there were not mathematics achievement difference of 11th grade students at SMKN 5 Mataram based on extrovert and introvert personalities.